2014
DOI: 10.21829/abm109.2014.195
|View full text |Cite
|
Sign up to set email alerts
|

Flora potencialmente útil de la selva tropical en la parte central de Veracruz, México: consideraciones para su conservación

Abstract: Tropical rainforests have been a valuable source of resources for human kind. However, this ecosystem is disappearing at an alarming rate, with only isolated fragments remaining in inaccessible zones and showing high probability of disappearing. The aim of this study was to identify tropical rainforest plant species with potential for human use in the central region of Veracruz, Mexico. A floristic inventory was compiled of rainforest fragments and secondary vegetation using the plotting method. The total area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Previous studies have shown that women usually have more knowledge about medicinal plants, and men know more about timber and handcraft species. This happens due to the sexual division of labour, and external factors resulting from the male migration of the young people inside the communities [18,21]. In our study, women on average cite two more plants and spend more money (17 plants, expenditure: $200) than their male counterparts (15 plants, expenditure: $176).…”
Section: Resultsmentioning
confidence: 64%
See 2 more Smart Citations
“…Previous studies have shown that women usually have more knowledge about medicinal plants, and men know more about timber and handcraft species. This happens due to the sexual division of labour, and external factors resulting from the male migration of the young people inside the communities [18,21]. In our study, women on average cite two more plants and spend more money (17 plants, expenditure: $200) than their male counterparts (15 plants, expenditure: $176).…”
Section: Resultsmentioning
confidence: 64%
“…Of the 85 indigenous people who answered the form, men represented the highest number (53%), and people from 70 to 85 years appeared to have a more extensive knowledge of these plants. In general, the gender was not significantly correlated to age and plant knowledge [18,19]. Even though all of the respondents generally used traditional plants, it has been common that, in many parts of the world, the women always demonstrate a more extensive knowledge in the use of plants [20].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Six of these 11 species were highlighted for promotion as a key species for reforestation in TP systems with scarce tree cover: P. schiedeana, which is important for auto consumption and as construction material [41], and C. sinensis due to its function as an edible product, firewood, and medicinal use. O. mexicanum is locally abundant; however worldwide, it is a threatened species which serves-besides its relative high commercial value [36]-as an important product for auto consumption, construction material, and firewood.…”
Section: Discussionmentioning
confidence: 99%
“…The predominant vegetation at the three drier sites is the seasonally dry tropical forest (i.e., forests subjected to prolonged dry season; [41]), while humid tropical forests dominate at the wettest end of the rainfall gradient. Floristically, Leguminosae is the most important family across studied sites [42][43][44], and the abundance of Leguminosae trees increases with the decrease in MAR.…”
Section: Study Areasmentioning
confidence: 99%